Role of Endothelial Cell Lipoprotein Lipase for Brown Adipose Tissue Lipid and Glucose Handling - Thiemann, Ellen; Schwaerzer, Gerburg K.; Evangelakos, Ioannis; Fuh, Marceline M.; Jaeckstein, Michelle Y.; Behrens, Janina; Nilsson, Stefan K.; Kumari, Manju; Scheja, Ludger; Pfeifer, Alexander; Heeren, Joerg; Heine, Markus (Frontiers in Physiology, 2022)
Cold-induced activation of brown adipose tissue (BAT) has an important impact on systemic lipoprotein metabolism by accelerating the processing of circulating triglyceride-rich lipoproteins (TRL). Lipoprotein lipase (LPL) expressed by adipocytes is translocated via endothelial to the capillary lumen, where LPL acts as the central enzyme for the vascular lipoprotein processing. Based on preliminary data showing that LPL is not only expressed in adipocytes but also in endothelial cells of cold-activated BAT, we aimed to dissect the relevance of endothelial versus adipocyte LPL for lipid and energy metabolism in the context of adaptive thermogenesis. By metabolic studies we found that cold-induced triglyceride uptake into BAT, lipoprotein disposal, glucose uptake and adaptive thermogenesis were not impaired in mice lacking Lpl exclusively in endothelial cells. This finding may be explained by a compensatory upregulation in the expression of adipocyte-derived Lpl and endothelial lipase (Lipg).